WHY SHOULD THE STATE INTERVENE IN THE LABOUR MARKET: THE CASE OF SOUTH AFRICA - Mokofe, William Manga (International Journal of Law in Changing World, 2022)
ABSTRACT Labour remains at the centre of political, social, and economic discourse in South Africa. Two broad perspectives dominate the political discourse as to why the state should intervene in the labour market. The first is the laissez-faire, free-market model, and the second, known as ‘social justice’ – a concept generally used to justify government intervention and the distribution of resources – is a perspective that stresses the need for social justice in the workplace in a variety of ways. This article explores which of these views will best protect workers – referred to in the context of the inadequacy of the contract as a mechanism to regulate the employment relationship – in an ever-changing South African labour market characterised by poverty, unemployment, inequality, the growth of the informal economy, an inflow of migrants, the digitalisation of the economy, and the impact of the Covid-19 pandemic. The author concludes by supporting the view that upholds social justice in the workplace.